Analysis on influencing factors of total retail sales of consumer goods in Hebei Province from 2010 to 2022 - Ma Hong; Oliver Valentine Eboy (Universiti Kebangsaan Malaysia, 2024)
The total retail sales of consumer products show how much people's living conditions have improved through time, as well as the extent to which their social commodity purchasing power has been realized and the state of urban consumption. In this paper, the ridge regression approach is utilized to analyze the relationship between the total retail sales of social consumer products and urban inhabitants’ per capita income, rural inhabitants’ per capita income, urban inhabitants’ per capita consumption expenditure, rural inhabitants’ per capita consumption expenditure, urbanization rate, the resident population at year-end, population density in Hebei province from 2010 to 2022. The findings indicate that urban inhabitants' per capita income has the biggest impact on the total retail sales of social consumer products in Hebei Province, while rural inhabitants' per capita consumption expenditure has the littlest effect. Finally, to sustain and healthy development of the domestic consumer market, four recommendations are made in light of the analyses' findings: (1) Encouraging businesses to actively support the codevelopment of the real economy and the online virtual economy. (2) The government should continue to reform the income distribution, narrow the income disparity between urban and rural regions, and promote the co-development of urban and rural regions, (3) The government should keep working to strengthen the system of social insurance and expand the coverage of social insurance, and (4) The government should create a good consumption environment, crack down on counterfeiting, punish illegal acts of counterfeiting and selling fakes, and ensure food safety.